VD_FINDINFO HC / 2010 / 677 vom 14. Dezember 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, BAIL À LOYER, ABUS DE DROIT | 257d CO, 274g al. 1 let. a CO, 457 CPC, 23 LPEBL, 29 LPEBL, 7 al. 2 RULV